Purification of Air Conditioner Waste into High Purity Water using Vacuum Distillation - Rachmad Ramadhan Yogaswara; Ketut Sumada; Erwan Adi Saputro (International Journal of Eco-Innovation in Science and Engineering, 2022)
The condensed water as a waste from air conditioner was purified in this study via vacuum distillation. Vacuum distillation can reduce the boiling point of water until 60oC decreasing the production cost of aquadest. This vacuum distillation aims to lower its mineral contents to meet quality standards of aquadest that is Total Dissolved Solid (TDS) 10 – 20 mg/L. The result of this study is TDS content of the aquadest reaching under 2 mg/L. The other parameter like conductivity and pH showed very low value, average at 4 μS/Cm and pH 7 fulfilling the requirement of high purity water. The vacuum distillation was proven to produce aquadest from air conditioner waste with high purity for many usefulness.